DAMPAK PANDEMI COVID-19 DAN PERUBAHAN POLA ADMINISTRASI TERHADAP PELAKU UMKM EKSPOR DAN IMPOR - Adi Kurnia, Candra (Al-Ijtima`i: International Journal of Government and Social Science, 2020)
Administration is an important part of doing business for both small and large businesses, including export and import business. CV. Donya Drop Daruet is one of the exporters and importers in Banda Aceh. The routine of this company experienced challenges during the Covid-19 Pandemic. This research uses qualitative research with observation data collection methods, interviews and supported by secondary data. The administrative pattern did not change significantly. However, there were changes to the technical implementation. The findings of this study have occurred that since the pandemic era, there have been technical changes in the implementation of export and import activities which were previously implemented in Aceh Province through Sultan Iskandar Muda Airport and export-import doers acting for and on their own behalf, but since the pandemic era, consolidator services and implementation processes were needed must be done through the Port of Belawan, North Sumatra. The changes in administrative patterns and the impact of the Covid-19 pandemic can be minimized if Aceh Government can maximize export-import services at loading ports in Aceh Province